Superguerrieri: L’influ-attivismo dei genitori caregiver tra rappresentazioni della disabilità e individualismo politico - Baffi, Alessandra; Binotto, Marco (Mediascapes journal, 2024)
The public representations of disability, the image provided by the media of people with disabilities, are central to determining identity, relationships, and possibilities for social inclusion. An increasingly large part of today's narrative about people with disabilities now takes place through digital platforms where individuals, often caregivers and family members, share their personal experiences and typically use them to propose an image of disability and promote forms of activism and cultural intervention. The research presented here analyzed communication, activities, and methods of activism proposed by a sample of caregiver parents of minors with serious illnesses or disabilities, through the study of their Instagram profiles, between 1 January 2021 and 31 December 2022. The general objective was to verify how this category of influ-activism produces both: a) a form of agency suited to the affordances of the platforms and mediatized voice; and b) creates content or information and a precise representation of their condition. The research results confirm that this case study represents a particularly indicative example of the affordances offered by the platforms, confirming the main hypotheses already emerging from the literature on the subject: i) the technical, media, and economic ecosystem built by the platforms is confirmed to favor the emergence of a kind of individualized activism, projects often directed towards a vocation for self-branding for specific and localized projects; and ii) algorithmic selection seems equally influential in expressive choices, the representations offered tend to resemble those present in other media: a neoliberal public commitment emerges, in which “adversity” is not overcome through a change in the social context but through motivation, performance, and individual merit.